Exploring the Impact of Artificial Intelligence on Learning and Decision-Making in Engineering Students - Kaur, Ranpreet; Dharmadhikari, Sonali Prasad; Bhagat, Hrishikesh; Yadav, Aakash; Gurav, Yogesh; Eldebeky, Sayed M. (Journal of Engineering Education Transformations, 2025)
Artificial intelligence (AI) adoption is rapidly increasing in several domains, and education is not an exception. One important breakthrough is the application of AI tools to teaching and learning activities that has shown great promise. They can serve as resources for students to use for a variety of academic purposes and decisions. As AI software, such as intelligent tutoring systems, chatbots, and learning boards driven by data, becomes pervasive within schools and universities, students are being given a more individualized, flexible, and responsive learning experience. The use of AI in engineering programs has its own advantages and disadvantages. Artificial intelligence technologies meet numerous roles in education. The growing use of AI in education and research has also led to ethical debate and ways to address it. The AI systems in this study are in dialogue with students and monitor student interactions, and collect such monitoring data. The findings reveal that users find AI useful for the understanding of new concepts, user-adaptive learning, and assistance in decision-making, but challenges regarding dependence, privacy, memory, and ethics persist. These potential negatives just highlight the need for moderation in terms of ethics, some teacher oversight on these types of programs, and keeping tabs on them. This study contributes to our understanding of how students use AI, giving important indications on what we should aim for in promoting responsible and effective use of AI in engineering education.